One day we could run out of non renewable resources while at the same time most of them cause damage to the environment
The answer to your question is B.
Answer:
The mean center of population is the place where an imaginary, flat, weightless, and rigid map of the United States would balance perfectly if all residents were of equal weight. Historically, the movement of the center of population has reflected the expansion of the country, the settling of the frontier, waves of immigration and migration west and south. Since 1790, the center of population has moved steadily westward, angling to the southwest in recent decades.
SOURCE: Geography Division, "Centers of Population Computation for the United States 1950-2010," issued March 2011, available at www.census.gov/geo/www/2010census/centerpop2010/COP2010_documentation.pdf. Consulted for historical reference: Historical Atlas of the United States, National Geographic Society, 1988.
NOTE: The Proclamation Line of 1763 limited British settlement to areas east of the Appalachian Mountains. Alaska and Hawaii were not included in the calculation of the mean center of population until 1950. Puerto Rico was not included in any decade. For more information on the mean center of population, an animated map, and other resources. This graphic is adapted from the "Census Atlas of the United States" published by the Census Bureau in 2007.
Explanation:
~Hello there!
Your question: <span>The viewpoint that past processes are the same as the present ones which created our present land surface is known as ________.
Your answer: </span>The viewpoint that past processes are the same as the present ones which created our present land surface is known as uniformitarianism.
Any queries ^?
Happy Studying! :D
Answer:
![k = -7](https://tex.z-dn.net/?f=k%20%3D%20-7)
Explanation:
Given
through (0,1) and (1,5)
through (0,-6) and (1,-2)
Required
Determine the value of k if f(x) is translated vertically down
To get the value of k, we perform the following operations.
For (0,-6) --- Substitute 0 for x and -6 for g(x) in ![g(x) = 5^x + k](https://tex.z-dn.net/?f=g%28x%29%20%3D%205%5Ex%20%2B%20k)
![g(x) = 5^x + k](https://tex.z-dn.net/?f=g%28x%29%20%3D%205%5Ex%20%2B%20k)
![-6 = 5^0 + k](https://tex.z-dn.net/?f=-6%20%3D%205%5E0%20%2B%20k)
![-6 = 1 + k](https://tex.z-dn.net/?f=-6%20%3D%201%20%2B%20k)
![k + 1 = -6](https://tex.z-dn.net/?f=k%20%2B%201%20%3D%20-6)
![k = -6 - 1](https://tex.z-dn.net/?f=k%20%3D%20-6%20-%201)
![k = -7](https://tex.z-dn.net/?f=k%20%3D%20-7)
For (1,-2) --- Substitute 1 for x and -2 for g(x) in ![g(x) = 5^x + k](https://tex.z-dn.net/?f=g%28x%29%20%3D%205%5Ex%20%2B%20k)
![g(x) = 5^x + k](https://tex.z-dn.net/?f=g%28x%29%20%3D%205%5Ex%20%2B%20k)
![-2 = 5^1 + k](https://tex.z-dn.net/?f=-2%20%3D%205%5E1%20%2B%20k)
![-2 = 5 + k](https://tex.z-dn.net/?f=-2%20%3D%205%20%2B%20k)
![k+5 = -2](https://tex.z-dn.net/?f=k%2B5%20%3D%20-2)
![k= -2-5](https://tex.z-dn.net/?f=k%3D%20-2-5)
![k = -7](https://tex.z-dn.net/?f=k%20%3D%20-7)
To further show that k = -7, we have the following:
When translated downward by 7 units, the function becomes
![g(x) = f(x) - 7](https://tex.z-dn.net/?f=g%28x%29%20%3D%20f%28x%29%20-%207)
Recall that:
and
So, we have:
![5^x + k = 5^x - 7](https://tex.z-dn.net/?f=5%5Ex%20%2B%20k%20%3D%205%5Ex%20-%207)
Subtract
from both sides
![5^x - 5^x + k = 5^x - 5^x + 7](https://tex.z-dn.net/?f=5%5Ex%20-%205%5Ex%20%2B%20k%20%3D%205%5Ex%20-%205%5Ex%20%2B%207)
![k = -7](https://tex.z-dn.net/?f=k%20%3D%20-7)